Before, during and after megafaunal extinctions: Human impact on Pleistocene-Holocene trophic networks in South Patagonia. (15th December 2020) - Pires, Mathias M.; Rindel, Diego; Moscardi, Bruno; Cruz, Livia R.; Guimarães, Paulo R.; dos Reis, Sergio F.; Perez, S. Ivan
Abstract: Worldwide extinctions of large terrestrial vertebrates in the late Pleistocene provide insight on how humans reshape ecological communities. Understanding the ecological causes and consequences of megafaunal extinctions requires integrating approaches to reconstruct the ecological communities from the past. Here, we combined archeological and paleontological evidence with network analyses to understand the changes in ecological communities from late Pleistocene to the Holocene in South Patagonia, the last continental region where the encounter between humans and extinct megafauna occurred. The zooarcheological record suggests humans would have interacted mainly with large-bodied species, which comprise a small subset of the available prey. Accordingly, using network reconstructions and structural analyses, we found that human arrival would have produced minor changes in the overall structure of trophic networks. However, those few novel interactions established by humans would have created multiple indirect paths among megafaunal species. Indirect paths are the route for indirect effects such as competition and increase the vulnerability of interaction networks to perturbations. After the extinctions of most of the megafauna, the impoverished network became structurally simpler and densely connected. Our reconstructions of past trophic networks show that multiple indirect effects, potentially contributing to extinctions, can emerge even from a limited number of novel interactions and illustrate how network organization can affect and be affected by extinctions events. Highlights: Studies on human impact on Pleistocene extinctions have focused on direct effects. Indirect effects mediated by species interactions can contribute to extinctions. We reconstruct past interaction networks from Patagonia and study their structure. Humans added a few direct links but multiple novel indirect paths among megafauna. Megafaunal extinctions reduced the structural complexity of trophic networks.